Comparison of the Quality of Life of COVID-19 Patients Cared for at Home and in the Hospital - Leili Yekefallah; Abbas Ahmadi; Rohollah Kalhor; Soheil Soltani; Peyman Namdar; Sareh Mohammadi (The Journal of Qazvin University of Medical Sciences, 2022)
Background: The demand for home care services has increased not only due to the increase in the elderly population but also due to consumer preference and technological advances that allow for the provision of sophisticated home care. Home healthcare services aim to help people improve their performance, live a more independent life, improve their well-being, and help them stay at home, and avoid hospitalization. Objective: This study was conducted to compare the quality of life (QoL) of COVID-19 patients under home care at a hospital in Qazvin City, Iran. Methods: his study was a cohort study. The samples included two groups of patients, hospitalized patients due to COVID-19 and patients with COVID-19 who received medical and nursing care at home. Patients were matched for age, underlying disease, and severity of the COVID-19 disease. In this study, a 3-month follow-up on changes in QoL compared to before hospitalization and receiving care at home was performed using a QoL questionnaire (SF-12). Findings: The mean score of QoL in the home care group was 32.36±2.15 and in the hospitalized group, it was 29.70±2.94, which shows a statistically significant difference, and the quality of home care patients reported to be higher than hospitalized patients (P<0.001, t=7.20) Conclusion: Receiving hospital care at home increases the QoL for patients with COVID-19. This finding can be generalized during different epidemics, and home care can be an excellent alternative to hospitalization for some patients.